A magnetic levitation-based tristable hybrid energy harvester for scavenging energy from low-frequency structural vibration. (15th October 2020) - Yang, X.; Wang, C.; Lai, S.K.
Highlights: A magnetic levitation-based hybrid energy harvester is proposed. A tri-stable mechanism is incorporated to enhance the working efficiency. The system works well under low-frequency excitation levels (3–8 Hz and 0.3–1 g). Portable electronics can be driven by the present harvester under low frequencies. Abstract: A magnetic levitation-based hybrid energy harvester is proposed in this work. The new harvester consists of a tri-stable nonlinearity-enhanced mechanism that not only enhances the energy transfer through resonant inter-well oscillations, and also offers a wider bandwidth under low-frequency excitation levels. This integrated unit that combines a slider-driven electromagnetic generator (EMG) and a sliding-mode triboelectric nanogenerator (TENG) can harness more energy from vibration motions, thus resulting in a higher power density. In this study, both theoretical modelling and experimental studies are presented to investigate the dynamic characterization of the mechanical design, in which only four outer magnets are deployed on a plane to establish a triple-well nonlinear behaviour. Magnetic forces of this harvester are calculated by the magnetizing current method and the formation of tri-stable potential wells in the dynamic system is verified by a bifurcation analysis. In addition, a prototype of the harvester is fabricated and tested by an electrodynamic shaker system. The results show that the prototype exhibits a frequency bandwidth of 3–8 Hz and generates an output power of 6.9 mW and 6.44 mW in both horizontal and vertical orientations at a frequency of 8 Hz and 1 g acceleration, respectively. A performance study is also conducted to show that the proposed technique can produce sufficient power output as compared to other electromagnetic-triboelectric devices.